INISIATIF PERENCANAAN TAMAN DI PONDOK PESANTREN "BBE"-BARENG, JOMBANG DALAM MENINGKATKAN KREATIVITAS DAN KEBERLANJUTAN - Suryaningsih, Dwie Retna; Thohiron, Moch.; Tojibatus S, Tatuk (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
Community service activities carried out at the "BBE" Bareng Islamic Boarding School, Jombang, aim to increase creativity and sustainability among students through the development of parks. The park is not only designed as a green space that beautifies the environment, but also as a means of education and self-development for students. Through systematic landscape planning, selecting plants that suit the microclimate, and arranging hardscape elements, this park is designed to optimally support the daily activities of students and create an environment that supports creativity and sustainability. Through gardening and plant care activities, students are not only taught the values ​​of responsibility and hard work, but also gain therapeutic benefits and psychological well-being. The use of economical plants also supports local economic empowerment, in accordance with the concept of sustainable Islamic boarding schools. Thus, this initiative not only improves the quality of life of santri, but also contributes to environmental conservation and empowerment of local communities